La voz de nuestra América: el sumak kawsay y la crítica intercultural al desarrollo (2021)
This article explores the philosophical aspects of Sumak Kawsay, understood as “good living”, that is, as a vital and ancestral commitment that is presented in the Andean civilizational order, emphasizing its critical potential against the hegemonic model of neoliberal society. At first, the term is linked to its linguistic meaning, to extract from there its sense; then, a conceptualization of “good living” is linked to its critical aspect; and finally, “good living” is presented from the perspective of indigenous philosophy and the debate that opens up there in relation to nature.